The Werther effect and its relationship with suicide attempts: a narrative review (Research, Society and Development, 2022)
Suicide is a complex topic and many variables can be involved in the problem. It is assumed that cases of suicide attempts could provide justifications for the act. Thus, this study sought to find evidence that supported or not the existence of the Werther effect, or contagion effect, in the current scientific literature. The objective of this narrativ review was to verify whether the available data confirmed an increase in suicide cases or attempts after a first case. The findings indicate that the effect is real and that it is closely related to the way in which the repercussion of a suicide occurs, in the traditional media or through other means.  The review found data that support the existence of the contagion effect in several parts of the world, in Europe, North America, and most of them in Asia, which indicates that the phenomenon is not restricted to a given culture. The narrativ review focused on four databases, in the last ten years, in Portuguese and English, and was evaluated by two researchers.